Preventing pneumococcal infections in patients with hematological malignancies: a review of evidence and recommendations based on modified Delphi consensus - Seth, Tulika; Melinkeri, Sameer; Dolai, Tuphan Kanti; Bhattacharyya, Jina; Sidharthan, Neeraj; Chakrabarti, Prantar; Malalur, Chaithanya; Taur, Santosh (Frontiers in Oncology, 2025)
IntroductionIndividuals with hematological malignancies (HMs) are at a high risk of invasive pneumococcal disease due to underlying malignancy and subsequent immunosuppressive anticancer therapy. Early management of pneumococcal infections is crucial for reducing morbidity and mortality in this vulnerable patient subgroup. In this study, we aim to review the current evidence and recommendations regarding the use of pneumococcal conjugate vaccines (PCVs) in patients with HMs and develop a consensus document on the optimal timing and patient profiles who can benefit from them.MethodsThe modified Delphi consensus method was used for achieving consensus. The panel comprised a scientific committee of six experts from India. Questions were drafted for discussion around: (i) the risk and consequences of pneumococcal disease in HMs; (ii) barriers to pneumococcal vaccination in the hemato-oncology clinical setting; and (iii) evidence and optimal timing of pneumococcal vaccines in HMs. The questionnaire was shared with the panel through an online survey platform (Delphi round 1). The consensus level was classified as high (≥80%), moderate (60%–79%), and low (< 60%). A Delphi round 2 meeting was conducted to discuss the questions that received near or no consensus to reach an agreement. The final draft of consensus statements was circulated among the experts for approval.ResultsPneumonia with or without bacteremia and bacteremia without foci of infection are the most frequently reported clinical presentations of pneumococcal infections in patients with HMs. A high risk of pneumococcal disease has been observed in patients with multiple myeloma (MM), acute myeloid leukemia (AML), acute lymphoblastic leukemia (ALL), and chronic lymphocytic leukemia (CLL). Priming with PCV enhances the response to pneumococcal polysaccharide vaccine 23 (PPSV23) in patients with HMs. Experts agreed that PCV is beneficial and can be strongly recommended in patients with CLL, MM, and patients undergoing hematopoietic stem cell transplantation. Children with acute lymphoblastic leukemia (ALL) would benefit from systematic revaccination with PCV after chemotherapy. The evidence is inadequate to consistently recommend pneumococcal vaccination to all patients with lymphoma, AML, and adults with ALL.ConclusionThis expert consensus will guide clinicians on the recommended approach for administering pneumococcal vaccination to patients with HMs.